Peningkatan Kesadaran Mitigasi Bencana Melalui Sosialisasi dan Penanaman Tumbuhan Endemik - Arfiudin Arfiudin; Azizi Aidytya Hidayatulah; Lodia Mailafiza; Muhammad Akil Mubtada; Tasya Yuliantika; Nadya Putri; Benny Firdaus Iskandar; Sabina Vianda; Rima Kurnia Lestari; Harya Anugrah Arrahman Wahid; Salsabila Crysanti Taswa (Universitas Muhammadiyah Enrekang, 2023)
Resam Lapis Village is one of the villages in Bantan District, Bengkalis Regency, Riau Province. This village has an area of 1,185 Ha which is dominated by peatland. Peatland is a type of soil that is prone to fire in the dry season. Therefore, appropriate mitigation measures are needed to prevent fires on peatlands considering that these lands are the source of livelihood for rural communities. Community socialization is a necessary step to increase public awareness in preventing fires on peatlands. After that, an implementation of the socialization is needed, such as planting pineapple seedlings to maintain water content in peatlands that are prone to burning. With this, it is hoped that the dissemination of knowledge and increased awareness of the people of Resam Lapis Village regarding disaster mitigation measures, especially fires on peatland, are appropriate.